THE TRANSLATION OF GENERIC INDONESIAN PLACE NAMES INTO ENGLISH ON THE OFFICIAL TOURISM WEBSITE - Raden Roro Shinta Felisia (Asosiasi Dosen Muda Indonesia, 2023)
The use of translation on a tourism website indicates that translation serves as a step to encourage tourists to learn about various places, particularly as tourist destinations. The website https://jakarta-tourism.go.id mentions various types of destinations or places, including museums, restaurants, markets, etc. Some articles on the website are available in both Indonesian (the source language) and English (the target language or translation). Through translation, tourists who cannot understand Indonesian but can understand English can still access information on numerous places. This research discusses the translation of generic Indonesian place names on the website. The results show preservation (15), transformation (53), and addition (3) strategies found in the translation of Indonesian generic place names. In titles, preservation (12), transformation (23), and addition (1) were observed. In paragraphs, preservation (3), transformation (30), and addition (2) were identified. This research hopes that the results will contribute to the tourism industry since tourism plays a significant role for relations among countries.